PENERAPAN MODEL INKUIRI BERBANTUAN MEDIA KOMPUTER TERHADAP MINAT BELAJAR KIMIA SMA NEGERI 4 PADANGSIDIMPUAN - Rizky Ariaji; Dakkal Harahap; Sahlan Tuah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
The type of research used in this study is a research experiment. The population in this research is the grade XI IPA SMA Negeri 4 Padangsidimpuan. Instruments used for data collection is a test of interest in learning chemistry in the form of essays and learning interest of students now. The test results obtained (1) there is a change of interest in learning chemistry being taught through the model of learning computer-assisted inkuiri media on the subject of reaction rates on the now interest the average experimental class students which of the 28 students There are 5 students or 18% interest rate which is at a